Impactos da legislação ambiental brasileira na exportação de camarão: um estudo com exportadores de camarão do Rio Grande do Norte - Pegado, Erika Araújo da Cunha (2006)
Brazilian exportations come growing in a constant form in the last years, stimulated for the globalization and public politics directed toward the increase of the internal surplus. In this context the objective of this work was to investigate the perception of the shrimp exporting entrepreneurs of Rio Grande do Norte, with relation to the impact of the Brazilian environmental legislation in the companies competitiveness at the external market. From data collected from the controllers of the companies, it was used a survey methodology, with exploratory and descriptive character. The results found in this study indicate that the companies, in general way, understand that the environmental legal requirements do not confuse nor help in the search and conquest of new international markets. A little more of the half of the researched companies, does not see the legislation rigid as important factor of competitiveness. However a sufficiently significant percentage, already has a more strategical vision on the subject, or at least already it heard to speak on such possibility